Biomimetic CO2 hydration activity of boronic acids. Issue 15 (13th April 2021) - Verma, Manju; Sai Phani Kumar, V.; Kumar, Shashi; Deshpande, Parag A.
Abstract : Inspired by the recent experimental reports on boron containing compounds to be active and biomimetic for carbon capture, we report the mechanistic details of CO2 hydration activities of boronic acids using density functional theory calculations. Abstract : Inspired by the recent experimental reports on boron containing compounds to be active and biomimetic for carbon capture, we report the mechanistic details of CO2 hydration activities of boronic acids using density functional theory calculations. Four boronic acids were analyzed, viz., [3-methyl-6-(1 H -pyrazol-1-yl)phenyl]boronic acid, 3-aminophenylboronic acid, 2, 6-dibromophenylboronic acid and 2, 6-bis(trifluoromethyl)phenylboronic acid. Free energy landscapes were developed for the hydration reaction. 2, 6-Dibromophenylboronic acid showed the highest turnover frequency. Computational NMR and FTIR spectra for various intermediates of the reaction were analyzed and compared with experimental spectra. The energetics as well as the spectral analyses confirmed the biomimetic mechanism for CO2 hydration over all the boronic acid catalysts under investigation.